Analisis Kepuasan Masyakarat Terhadap Alokasi BBM Bersubsidi Di Kecamatan Johan Pahlawan Aceh Barat - Melani Febriyanti; Mirdha Fahlevi (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2021)
Abstract This study aims to analyze the fuel subsidized by the government, subsidized fuel is needed by the people in the district of Johan Pahlawan, especially for fishermen and people who have low incomes. Questionnaires were distributed throughout the district of Johan Pahlawan, West Aceh. Sampling was carried out by considering the representativeness of respondents from each Kec.Johan Pahlawan, as many as 47 respondents in online media. This data was analyzed by using a quantitative approach, with the technique of collecting data according to the truth and then the data was processed, compiled and analyzed by the method of descriptive statistics. Keywords: community satisfaction, subsidized fuel